New bipolar host materials for high performance of phosphorescent green organic light-emitting diodes - Kim, Gyeong Heon; Lampande, Raju; Kong, Ji Hoon; Lee, Jung Min; Kwon, Jang Hyuk; Lee, Jae Kyun; Park, Jung Hwan (ROYAL SOC CHEMISTRY, 2015)
We report a series of four bipolar host materials with indenocarbozole and biphenyl pyrimidine moieties for efficient phosphorescent green organic light-emitting diodes (OLEDs). All four host materials possess excellent electro-optical properties as well as good thermal and morphological stability due to their high glass transition temperature of 129 degrees C and decomposition temperature of 363-401 degrees C. The new materials also show good triplet energy of 2.76 eV and excellent charge carrier transport properties. The fabricated OLED device with 11-[3-(2,6-diphenyl-pyrimidin-4-yl)-phenyl]-12,12-dimethyl-11,12-dihydro-11-aza-indeno[2,1-a]fluorene (mDPPICz1) as green host shows maximum current and power efficiency as high as 75.8 cd A(-1) and 87.1 lm W-1 at 1000 cd m(-2), and an almost ideal external quantum efficiency of 21.7%.
Keywords: EFFICIENT GREEN; BLUE; OLEDS; DENSITY; ENERGY; DERIVATIVES; DEVICES; COMPLEXES; EXCHANGE; PHOLEDS